Distal renal tubular acidosis: ERKNet/ESPN clinical practice points. Issue 9 (29th April 2021) - Trepiccione, Francesco; Walsh, Steven B; Ariceta, Gema; Boyer, Olivia; Emma, Francesco; Camilla, Roberta; Ferraro, Pietro Manuel; Haffner, Dieter; Konrad, Martin; Levtchenko, Elena; Lopez-Garcia, Sergio Camilo; Santos, Fernando; et al.
Abstract: Distal renal tubular acidosis (dRTA) is characterized by an impaired ability of the distal tubule to excrete acid, leading to metabolic acidosis. Associated complications include bone disease, growth failure, urolithiasis and hypokalaemia. Due to its rarity, there is limited evidence to guide diagnosis and management; however, available data strongly suggest that metabolic control of the acidosis by alkali supplementation can halt or revert almost all complications. Despite this, cohort studies show that adequate metabolic control is present in only about half of patients, highlighting problems with treatment provision or adherence. With these clinical practice points the authors, part of the working groups tubulopathies in the European Rare Kidney Disease Reference network and inherited kidney diseases of the European Society for Paediatric Nephrology, aim to provide guidance for the management of patients with dRTA to facilitate adequate treatment and establish an initial best practice standard against which treatment of patients can be audited.